Cardiovascular Risk Assessment Using Updated WHO/International Society of Hypertension Risk Prediction Charts and Atherosclerotic Cardiovascular Disease Risk Score in Residents of Amreli District - Trusha Kansagara; Nitin A. Lodha; Yamini J. Gurjar (Indian Association of Preventive and Social Medicine, 2023)
Introduction: India is one of the countries the World Health Organization (WHO) has recognized as having the majority of lifestyle-related illnesses in the near future. The highest incidence of CVD are found on the Indian subcontinent. Objectives:To assess the cardiovascular risk among adults aged >40 years using the updated WHO/ISH risk prediction charts and ASCVD risk score and to compare baseline cardiovascular risk estimation by both risk scores. Method: This cross-sectional study was done among 228 individuals aged 40-74 years of urban and rural areas. A semi-structured interviewer administered questionnaire was developed. The data was collected in Epicollect 5 mobile application and analyzed using Jamovi software. Results:The mean age of the study participants was 56.54 ±0.73 years. CVD high risk was signiicantly higher in males as compared to females (P<0.05). The ASCVD risk score classiied (38.2%), of the participants as high-risk, whereas the lab-based and non lab-based versions of WHO/ISH risk prediction classiied less than 10% as high risk. There was moderate agreement between the lab-based and non lab-based versions of the WHO/ISH risk prediction (Kappa-0.724, p-0 .000), fair between ASCVD risk score and non lab-based versions of the WHO/ISH (Kappa-0.310, p-0.000). The agreement between, ASCVD risk score and lab-based version of WHO/ISH risk predictor was fair (Kappa-0.309, p-0 .000). Conclusion: In current study, it was observed that one-third of the participants had a high risk of CVD events based on the ASCVD risk score, and a smaller number of participants were found to be at high risk according to the WHO/ISH risk chart. So we need to implement this risk scores predictors of CVD events for identify the high risk individual and their further management.